2010
DOI: 10.1080/09540121.2010.482125
|View full text |Cite
|
Sign up to set email alerts
|

“It took a piece of me”: initial responses to a positive HIV diagnosis by Caribbean people in the UK

Abstract: How do people respond to the news that they are HIV positive? To date, there have been few published qualitative studies of HIV diagnosis experiences, and none focusing on Caribbean people. Twenty-five HIV-positive Caribbean people in London, UK, related their diagnosis experience and its immediate aftermath in semi-structured interviews. Diagnosis with HIV caused profound shock and distress to participants, as they associated the disease with immediate death and stigmatisation. The respondents struggled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 19 publications
7
53
0
1
Order By: Relevance
“…Others have also noted that responses to receiving a positive test result often include denial, anxiety, depression and suicidal ideation (Coates, Moore, & McKusick, 1987;Ostrow et al, 1989) and that the period immediately following diagnosis is a particular point of vulnerability for depression (Ciesla & Roberts, 2001). More recent research not only highlights the on-going distress associated with diagnosis itself, but also the particular importance of how test results are communicated (Anderson et al, 2010;Hult, Maurer, & Moskowitz, 2009). This study has findings reminiscent of the pre-ART literature which highlighted the psychological needs of those newly diagnosed.…”
Section: Discussionmentioning
confidence: 91%
“…Others have also noted that responses to receiving a positive test result often include denial, anxiety, depression and suicidal ideation (Coates, Moore, & McKusick, 1987;Ostrow et al, 1989) and that the period immediately following diagnosis is a particular point of vulnerability for depression (Ciesla & Roberts, 2001). More recent research not only highlights the on-going distress associated with diagnosis itself, but also the particular importance of how test results are communicated (Anderson et al, 2010;Hult, Maurer, & Moskowitz, 2009). This study has findings reminiscent of the pre-ART literature which highlighted the psychological needs of those newly diagnosed.…”
Section: Discussionmentioning
confidence: 91%
“…29,30 Certainly, as in other studies, the HIV diagnosis experience caused a ''biographical disruption'' for many of our participants, in which they struggled to form a cohesive sense of self and feared how others might perceive them. 31,32 For our participants, there was no obvious relationship between disclosure and engagement in care, and we found that participants could develop a medical HIV identity (i.e., seek HIV care), without developing a positive view of this identity or integrating it with a social HIV identity. However, positive experiences with disclosure helped participants to identify as an HIV-positive person, while feared or actual negative experiences with disclosure clearly affected their psychological well-being.…”
Section: Discussionmentioning
confidence: 95%
“…Time of HIV diagnosis can often be marked by maladaptive coping strategies to the stressful event. Affective responses during this period can range from fear of death [27] and ostracism [28], to complete denial [29] of the disease and intense anger towards oneself and others. Behavioral responses, though not all negative, can range anywhere from an ‘autopilot’ reaction to highly self-destructive behavior involving substance use and acting out sexually [30].…”
Section: Discussionmentioning
confidence: 99%